Mastering Islamic finance a practical guide to Sharia-compliant banking, investment and insurance - Karbani, Faizal (Pearson, 2015)
Mastering Islamic Finance will give practitioners an understanding of Islamic finance, from the basic techniques, through to advanced applications. Helping to demystify and clarify the differences with conventional banking, it will enable practitioners to develop Sharia compliant products for customers.